2022
DOI: 10.3389/fnagi.2022.877078
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Integration in Mice With Parkinson’s Disease and the Intervention Effect of Cyanidin-3-O-Glucoside

Abstract: BackgroundParkinson’s disease (PD) is a multifactorial degenerative disease of the central nervous system, which affects mostly older adults. To date, research has focused on the progression of PD. Simultaneously, it was confirmed that the imbalances in gut microbiota are associated with the onset and progression of PD. Accurate diagnosis and precise treatment of PD are currently deficient due to the absence of effective biomarkers.MethodsIn this study, the pharmacodynamic study of cyanidin-3-O-glucoside in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Kaewmool et al obtained similar results studying the effects of Cyanidin 3-O-glucoside, anthocyanins responsible for the red and blue pigments of different fruits and well known for its neuroprotective effects [138]. Authors demonstrated that cyanidin treatment (2.5-5-10 µM) for 4 h inhibits the NF-κB and p38 pathways, thus affecting the expression of pro-inflammatory cytokines in microglial BV2 cells [138,139].…”
Section: Flavonoids and Neurodegenerative Diseases: Role Of Nf-κb Sig...mentioning
confidence: 77%
“…Kaewmool et al obtained similar results studying the effects of Cyanidin 3-O-glucoside, anthocyanins responsible for the red and blue pigments of different fruits and well known for its neuroprotective effects [138]. Authors demonstrated that cyanidin treatment (2.5-5-10 µM) for 4 h inhibits the NF-κB and p38 pathways, thus affecting the expression of pro-inflammatory cytokines in microglial BV2 cells [138,139].…”
Section: Flavonoids and Neurodegenerative Diseases: Role Of Nf-κb Sig...mentioning
confidence: 77%
“…Cyanidin 3-O-glucoside belongs to the anthocyanins class; it is present in plants such as berries and soybean fruits, where it is responsible for the red, purple, and blue pigments. Cyanidin has been reported to act as neuroprotector in several disorders, such as AD, Parkinson’s disease, and multiple sclerosis [ 211 , 212 , 213 , 214 , 215 ]. The anti-AD effect is evidenced in the inhibition of Aβ amyloid accumulation.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Integrating multi-omics data is crucial for gaining a comprehensive understanding of complex diseases like Alzheimer’s [ 1 ], Parkinson’s [ 2 , 3 ], and cancer [ 4 ]. However, it is a difficult task that requires advanced computational methods.…”
Section: Introductionmentioning
confidence: 99%